Political meanings of national belonging: tracing the evolution of 'Polishness' in the Third Republic of Poland. (22nd March 2021) - Klajn, Maryla
Recent years have been marked by the rise of populist anti-immigrant movements throughout the world. Poland has become one of the most notorious anti-immigration states in the European Union, with its current government continuously calling for stricter border controls and systematically embracing a hard-line nationalist discourse. The concept of 'Polishness', or Polish national identity, is frequently used to legitimise political decision-making and belief in protection of a socio-cultural homogeneity fuels discussions for securitisation of the national borders. This article analyses the evolution of the meaning of Polishness and its instrumentalisation in the political discussions about border protection in the Third Republic of Poland. Deploying critical discourse analysis in examination of the Polish Sejm parliamentary debates on border-related laws 1989-2018, this paper links the political discussions about the physical national borders with the broader political discourse of Polishness and national belonging.